Pengaruh Rasio Likuiditas, Rasio Solvabilitas, Rasio Profitabilitas, dan Rasio Aktivitas Terhadap Perubahan Laba Pada Industri Farmasi - dina, dhea salsabila; hariyono, anwar (Universitas Muhammadiyah Gresik, 2024)
This study aims to examine how influential the Liquidity Ratio, Solvency Ratio, Liquidity Ratio and Profitability Ratio have on Profit Changes in the Pharmaceutical Industry Listed on the Indonesian Stock Exchange in 2016-2020. This type of research is quantitative by taking data on company financial reports that have been published on the Indonesia Stock Exchange. The theory used in this research is Signaling Theory. The sampling method used purposive sampling technique. The samples used in this study were 10 pharmaceutical companies listed on the Indonesia Stock Exchange. With a total of 50 data with a period of 5 years. The analytical method used is multiple linear analysis supported by IBM SPSS Statistics version 25. The results of this study indicate that the Activity Ratio variable has an effect on earnings changes. However, the Profitability Ratio has a negative effect on Profit Changes, while the Liquidity Ratio and Solvability Ratio have no effect on Profit Changes at all.